Effect of alumina on thermodynamic performance of palladium-H2 (D2) system. (12th May 2022) - Jiang, Yingwu; Ji, Fuhao; Feng, Yongjun; Ye, Xiaoqiu; Ni, Muyi
Abstract: Palladium (Pd) has a strong hydrogen isotope effect, widely used in the Thermal Cycling Absorption Process (TCAP) separation column. However, due to pulverization and high gas resistance, Pd was usually dispersed in backing materials, such as alumina (Al2 O3 ), to improve the service performance. In this paper, the microstructure of sponge palladium and Pd–Al2 O3 pellet was observed by Scanning Electron Microscopy (SEM), and the crystalline structure before and after hydrogeneration was characterized by X-Ray Diffractometer (XRD). To study the support effect of backing material Al2 O3 on the hydrogen/deuterium thermal absorption performance of palladium, the pressure-composition-temperature (P–C-T) curves were measured by series experiments. The result shows that Al2 O3 acts as a support material between palladium particles to suppress the effect of the pellet expansion-shrinking during H2 (D2 ) absorption/desorption cycling. Alumina could provide free position for hydrogen atoms. And the inflection points of α phase to α+β phase shift from 0.02 to 0.09 for Pd–Al2 O3 pellet/hydrogen system. The entropy and enthalpy variation of Pd/H (Pd/D) system in α+β phase are respectively −18.34 (−16.83) kJ/mol and −45.65 (−42.44) J/mol/K, which show no correlation with alumina. The H-D separation factor positively correlates with the quantity of hydrogen in the solid phase, and alumina could restrain the separation effect. Highlights: Al2 O3 has inhibitory effect on H-D separation factor while Q/M ratio> 0.32. Al2 O3 influences the P-C-T distribution of Q-Pd system. Al2 O3 has no contribution to the entropy and enthalpy variation of Q-Pd system.